Central monitoring of depression and anxiety symptoms reduces placebo responses in depression clinical trials: A post hoc exploratory analysis of data from the phase III CCT‐004 trial of vortioxetine - Yoshinori Watanabe; Akira Nishimura; Toshiaki Kikuchi; Norifusa Sawada; Manami Imazaki; Isao Inada; Koichiro Watanabe (Wiley, 2022)
Abstract Aim Clinical trials of antidepressants often fail to demonstrate their efficacy versus placebo, suggesting that patient selection based on physician ratings of depression may contribute to a high placebo response. Methods In the CCT‐004 trial of vortioxetine, central monitoring was employed to compare physician and patient ratings of depression and anxiety at baseline and over time to identify factors contributing to a large placebo response, as well as to explore the potential of a unique patient‐rated clinical measure combining QIDS‐J and Himorogi Self‐rating Anxiety Scale (HSAS), to contribute to optimal patient selection at baseline and patient monitoring over time. Results The CCT‐004 trial showed similar trends between the QIDS‐J and MADRS (Montgomery‐Åsberg Depression Rating Scale) ratings. It was suggested that central monitoring of the QIDS‐J and MADRS ratings of depression and anxiety symptoms helped reduce the baseline score inflation by calling the study sites' attention to discrepancies between these ratings at baseline; it also allowed these ratings to be assessed for their concordance over time. Of note, MDD patients with baseline QIDS‐J scores ≥11/HSAS ≤19 were associated with the smallest placebo response, with the effect size being larger than that for those with QIDS‐J scores ≤10/HSAS ≥20. Conclusion The use of both physician and patient ratings of depression and anxiety symptoms at baseline and over time, as well as their central monitoring, helped minimize the baseline score inflation and optimize patient monitoring over time, and allowed the antidepressant to be evaluated for its full therapeutic potential.